2004
DOI: 10.3748/wjg.v10.i9.1321
|View full text |Cite
|
Sign up to set email alerts
|

Hyperammonemia, brain edema and blood-brain barrier alterations in prehepatic portal hypertensive rats and paracetamol intoxication

Abstract: AIM:To study the blood-brain barrier integrity, brain edema, animal behavior and ammonia plasma levels in prehepatic portal hypertensive rats with and without acute liver intoxication. METHODS:Adults male Wistar rats were divided into four groups. Group I: sham operation; II: Prehepatic portal hypertension, produced by partial portal vein ligation; III: Acetaminophen intoxication and IV: Prehepatic portal hypertension plus acetaminophen. Acetaminophen was administered to produce acute hepatic injury. Portal pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 19 publications
3
24
0
Order By: Relevance
“…In previous experiments with this rat model, alterations in the CNS have been documented, including BBB permeability modifications [5,20] . The impact of PH on the BBB has been demonstrated in rats, in which, 40 d after portal vein stricture, the BBB recovers its function associated to normalize portal pressure and the impermeability to dyes [20] .…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In previous experiments with this rat model, alterations in the CNS have been documented, including BBB permeability modifications [5,20] . The impact of PH on the BBB has been demonstrated in rats, in which, 40 d after portal vein stricture, the BBB recovers its function associated to normalize portal pressure and the impermeability to dyes [20] .…”
Section: Discussionmentioning
confidence: 80%
“…HE in acute and chronic liver disease is a complex syndrome, associated frequently with hyperammonemia. Increases in blood brain barrier (BBB) permeability present in PH, allow ammonia ions and other neurotoxic substances to penetrate brain tissue [3][4][5][6] . Hyperammonemia is caused by a defect in the liver parenchyma that forms urea from intestinal nitrogenic substances, and vein shunts from the splanchnic circulation carry it into the general circulation [7] .…”
Section: Introductionmentioning
confidence: 99%
“…As we previously described, high ammonia blood concentrations exist in prehepatic PH rats [5][6][7] . Because of that, and in order to maintain the hyperammonemic milieu, 100 M ammonium acetate was added to both, the preincubation and incubation media, only to the APs from PH rats.…”
Section: Ex Vivo Studiesmentioning
confidence: 99%
“…Several substances have been proposed as mediators of this hypodynamic circulatory state including glucagon, prostacyclins and endotoxin, especially nitric oxide (NO) [2][3][4] . Furthermore, we have demonstrated that PH rats are a subclinic model of PSHE, since rats with PH have hyperammonemia, electrophysiology alterations, blood-brain barrier breakdown, astrocyte alterations; changes in catecholamine uptake and hippocampal mitochondrial dysfunction [5][6][7][8][9] . In addition, the relationship between hyperammonemic syndromes and enhanced NO production by increased neuronal NO synthase (nNOS, a NOS enzyme isoform) protein expression in different brain regions is well known [10,11] .…”
Section: Introductionmentioning
confidence: 99%
“…Our laboratory has shown [94] that the altered integrity of BBB gets back to normal in a HE��PVL induced model after portal pressure returns to a normal value. Moreover, in a group of animals with por�� tal hypertension (PVL��induced) plus acetaminophen, be�� havioral changes and increased the BBB alterations were observed [95] . Therefore it can be concluded that the BBB is an area where further research is needed to integrate all components and generate a view of the totality in HE.…”
Section: Blood Brain Barrier Brain Barrier Brain Barriermentioning
confidence: 99%